2022
DOI: 10.21203/rs.3.rs-1283482/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probiotics are a good choice for the treatment of Bacterial Vaginosis: a meta-analysis of randomized controlled trial

Abstract: Background: Bacterial vaginosis is one of the most common vaginal infectious diseases in female reproductive period. Although the existing view is that probiotic treatment may be one of the feasible methods for the treatment of bacterial vaginosis, different intervention methods lead to different treatment results. Therefore, up-to-date and comprehensive evidence in this regard is essential for the development of intervention strategies.Objective: This meta-analysis aims to systematically evaluate the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Similar to our results, a probiotic administration for a 10-day duration resulted in a significant reduction of pathogenic microbiota in vagina and the maintenance of vaginal eubiosis up to 30 days after the end of treatment, regardless of the route of administration (48). In contrast, a recent systematic review found that Lacticaseibacillus rhamnosus administered orally was more efficacious than intravaginal application for the treatment of BV (49), which was again likely to be due to unstandardized methodology mentioned above. A narrative review had concluded that the administration of selective probiotic strains resulted in enhanced host's ability to fight existing infection, restoration of normal vaginal flora and prevention of further BV recurrence when given at a dosage of over 100 million CFU for 2 months (50).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to our results, a probiotic administration for a 10-day duration resulted in a significant reduction of pathogenic microbiota in vagina and the maintenance of vaginal eubiosis up to 30 days after the end of treatment, regardless of the route of administration (48). In contrast, a recent systematic review found that Lacticaseibacillus rhamnosus administered orally was more efficacious than intravaginal application for the treatment of BV (49), which was again likely to be due to unstandardized methodology mentioned above. A narrative review had concluded that the administration of selective probiotic strains resulted in enhanced host's ability to fight existing infection, restoration of normal vaginal flora and prevention of further BV recurrence when given at a dosage of over 100 million CFU for 2 months (50).…”
Section: Discussionsupporting
confidence: 84%
“…A recent pilot clinical study that investigated the probiotic potential of Lacticaseibacillus 10.3389/fnut.2022.938838 rhamnosus had exhibited the strain to have broad adverse activities against vaginal pathogens, in vitro capability to adhere to VK2/E67 vaginal epithelial cells, and antioxidant properties as demonstrated by the strain's ability to resist linoleic acid peroxidation. Furthermore, the strain was also shown to have anti-inflammatory properties in which gene expressions of COX-2 and the proinflammatory interleukin-8 were downregulated, whereas the expression of the anti-inflammatory interleukin-10 was upregulated (49).…”
Section: Discussionmentioning
confidence: 99%